Metal Coating Synthesized by Inkjet Printing and Intense Pulsed-Light Sintering - Meng, Fanbo (Materials (Basel), 2019)
The inkjet printing of nanoparticle inks to produce metal coatings is low in manufacturing cost and high in efficiency compared to conventional methods such as electroplating and etching. However, inkjet-printed metal coatings require sintering to provide better metal conductivity and adhesion. Traditional sintering methods require high processing temperatures that can easily damage the coating substrate. In this study, an enhanced overall conductivity is achieved by sintering a nanoparticle metal coating with intense pulsed light. Metal coatings sintered using different parameters were characterized by a profilometer and a four-probe tester, which showed that the surface topographies differed with different sintering degrees. The adhesion of the metal coating was proportional to the pre-sintering temperature within the allowable range of the substrate. Finally, the optimization of the sintering process according to the experimental results improved both the electrical conductivity and adhesion of the metal coating. The optimized parameters were used to fabricate a microstrip antenna and perform the return loss test and microwave darkroom test. The results matched the simulation results well.